1996
DOI: 10.1287/mnsc.42.11.1515
|View full text |Cite
|
Sign up to set email alerts
|

Decision Quality Using Ranked Attribute Weights

Abstract: Three published approximation formulae for selecting the best multiattribute alternative based on rank-ordered weights are evaluated. All formulae are surprisingly efficacious in determining the best multiattribute alternative. Rank order centroid (ROC) weights are more accurate than the other rank-based formulae; furthermore, the ROC formula generalizes to incorporate both other forms of partial information about attribute weights and partial rank order information as well. Because a ROC-based analysis is so … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
349
0
10

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 544 publications
(365 citation statements)
references
References 17 publications
6
349
0
10
Order By: Relevance
“…To aggregate the product factors to a single value for the design aspect assessment, we suggest forming relevance rankings based on available data or expert opinion. We use the Rank-Order Centroid method [32] to calculate the weights automatically from the relevance ranking according to the Swing approach [33]. This function returns a value between 0 and 10 that needs to be read differently compared with the previous evaluation results.…”
Section: Deficient Encapsulation @Class;1mentioning
confidence: 99%
“…To aggregate the product factors to a single value for the design aspect assessment, we suggest forming relevance rankings based on available data or expert opinion. We use the Rank-Order Centroid method [32] to calculate the weights automatically from the relevance ranking according to the Swing approach [33]. This function returns a value between 0 and 10 that needs to be read differently compared with the previous evaluation results.…”
Section: Deficient Encapsulation @Class;1mentioning
confidence: 99%
“…Second, the assessor may rank weights. Rank order centroid (ROC) weights [75] have been found to give good estimates [76] in which w min = 1/n² and so α = 1/(1+n²).…”
Section: Non-judgemental Analysismentioning
confidence: 99%
“…Barron and Barret [4] studied algebraic formulas such as equal weights and the use of ROC (rank order centroid) weights to select a representative weights vector w from a set of admissible weights W, with the purpose of using w to evaluate the alternatives. These authors concluded that ROC weights provide a better approximation than the other weighting vectors they considered.…”
Section: A Reviewmentioning
confidence: 99%
“…Usually this is studied using Monte-Carlo simulations: randomly generating a large number of problems (criteria weights and value of each alternative in each criterion), determining the alternative with the highest multiattribute value, and comparing this alternative with the alternative chosen by the rule being studied, which uses only part of the information. Examples of such comparisons can be found in [4,[40][41][42]. However, these references consider that only the weights are unknown, and it is important to extend this idea to situations where the values of the alternatives in each criterion are also unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation